Analysis of the Nature of Science in Elementary School Science Curriculum and Its Empowerment in Student Book - Lungguh Puri Pramswari; Sabila Idzni Suryana; Ari Widodo; Devi Septiani Putri (Postgraduate, University of Mataram, 2021)
The nature of Science or NOS is the knowledge that explains how science works and how scientists conduct research. The nature of science has aspects in the form of form and nature, namely aspects of the product, scientific attitude, process, subjective, tentative, empirical, Theory and Law, Social and Culture, Creativity, Scientific Method. It is important to convey aspects of the nature of science into the science curriculum and student books because they are a reference in the learning process so that learning objectives can be achieved properly. Submission of aspects of the nature of good science is to convey it correctly and explicitly. Based on the analysis and comparison results, it shows that aspects of the nature of science in the elementary school curriculum and its embodiment in student books are not explained explicitly, both in the curriculum and in student books. The results of the percentage value of the essence of science in the student curriculum have a value of > 80%, namely product, subjective, creative aspects, and in the student's book, only product aspects have a percentage value of > 80%. Meanwhile, other aspects have a low percentage value of <80%.